Analysis of Chemical Equilibrium of Silicon-Substituted Fluorescein and Its Application to Develop a Scaffold for Red Fluorescent Probes - Hirabayashi, Kazuhisa; Hanaoka, Kenjiro; Takayanagi, Toshio; Toki, Yuko; Egawa, Takahiro; Kamiya, Mako; Komatsu, Toru; Ueno, Tasuku; Terai, Takuya; Yoshida, Kengo; Uchiyama, Masanobu; Nagano, Tetsuo; et al. (Analytical chemistry (Washington), 2015)
Fluorescein is a representative green fluorophore that has been widely used as a scaffold of practically useful green fluorescent probes. Here, we report synthesis and characterization of a silicon-substituted fluorescein, i.e., 2-COOH TokyoMagenta (2-COOH TM), which is a fluorescein analogue in which the O atom at the 10′ position of the xanthene moiety of fluorescein is replaced with a Si atom. This fluorescein analogue forms a spirolactone ring via intramolecular nucleophilic attack of the carboxylic group in a pH-dependent manner. Consequently, 2-COOH TM exhibits characteristic large pH-dependent absorption and fluorescence spectral changes: (1) 2-COOH TM is colorless at acidic pH, whereas fluorescein retains observable absorption and fluorescence even at acidic pH, and the absorption maximum is also shifted; (2) the absorption spectral change occurs above pH 7.0 for 2-COOH TM and below pH 7.0 for fluorescein; (3) 2-COOH TM shows a much sharper pH response than fluorescein because of its pK a inversion, i.e., pK a1 > pK a2. These features are also different from those of a compound without the carboxylic group, 2-Me TokyoMagenta (2-Me TM). Analysis of the chemical equilibrium between pH 3.0 and 11.0 disclosed that 2-COOH TM favors the colorless and nonfluorescent lactone form, compared with fluorescein. Substitution of Cl atoms at the 4′ and 5′ positions of the xanthene moiety of 2-COOH TM to obtain 2-COOH DCTM shifted the equilibrium so that the new derivative exists predominantly in the strongly fluorescent open form at physiological pH (pH 7.4). To demonstrate the practical utility of 2-COOH DCTM as a novel scaffold for red fluorescent probes, we employed it to develop a probe for β-galactosidase.